The use of Artificial Intelligence and 3D bio-printing for organ transplants - D’Alessandro, Aline Almeida Barbaresco; D’Alessandro, Walmirton Bezerra; Herrera, Sávia Denise Silva Carlotto; Mendes, Seyna Ueno Rabelo; Paiva, Maykon Jhuly Martins de; Junior, Osvaldo Gonçalves Barbosa; Holanda, Francisco de Sousa; Pedreira, Layra Eugenio; Lima, Mariana Gomes de; Santos, Isamara Alves dos (Seven Editora, 2024)
Technological evolution is driving revolutionary changes in the healthcare sector, especially in the field of organ transplants. Crucial innovations in this field include Artificial Intelligence (AI) and 3D printing, which, when combined, are paving the way for remarkable advancements in the creation of organs for transplants. This evolution has the potential to radically transform regenerative medicine and the treatment of chronic diseases. AI plays a fundamental role in processing and analyzing large amounts of data to optimize the design and functionality of artificial organs. It assists in modeling complex organic structures, predicts organ reactions in various environments, and facilitates the customization of organs according to the specific needs of patients. Furthermore, AI contributes to improving manufacturing processes and reducing costs, making the technology more accessible and effective. On the other hand, 3D printing, also known as bio-printing, enables the construction of three-dimensional structures using successive layers. In regenerative medicine, it is used to manufacture artificial organs and tissues from living cells. This technique has the potential to alleviate the shortage of donated organs, reducing dependence on human donors and the risk of transplant rejection, as organs can be created from the patient's own cells. The fusion of AI with 3D printing in organ transplant production is a promising field with enormous potential to save lives and improve the quality of life for patients. This interdisciplinary approach is redefining the boundaries of tissue and organ engineering, opening new horizons in the customization of medicine, research, and medical ethics. With the continuous advancement of these technologies, more significant progress is expected in the coming years. DOI:https://doi.org/10.56238/sevened2024.001-009